Site Suitability Analysis for Urban Settlements along River Jhelum, Pakistan using GIS and Remote Sensing Techniques - Sahar Zia; Muntaha Mohsin; Muhammad Nasar-u-Minallah; Aysha Hanif (Faculty of Geography, Universitas Gadjah Mada, 2022)
Infrastructure development is critical to the success of economic growth policies. Remote sensing and GIS tools have an important role to play in the development of various urban infrastructures. Due to the rapid growth of urban population and urbanization, it is necessary to find out the site's suitability for sustainable urban development. The main aim of the study is to study the growth and trend of urbanization, as well as to find out the suitable sites for further urban development in northern Punjab, along the river Jhelum, Pakistan. The study illustrates the use of geographic information system (GIS) and Remote Sensing based techniques i.e. Human Natural Environment Index (HNEI) applied with a foundation of Relief Degree of Land Surface (RDLS), Temperature Humidity Index (THI), Water Resource Index (WRI), and Land Cover Index (LCI) for selection of the suitable site for urban settlements along river Jhelum, Pakistan. For this purpose, Toposheet and Landsat satellite data were used to generate various thematic layers using ArcGIS software. The results were generated in form of five categories i.e., highly suitable, moderately suitable, relatively low suitable, low suitable, and non-suitable. The final results indicated that district Sargodha is most suitable for long-term sustainable urban settlements favored by relief, climate, water availability, land cover scenario, and flood hazard-free area. Eventually, a site suitability map is prepared for further urban development. The present study allows the local people as well as urban planners for the appropriate plans of land use planning in sustainable urban development.